Somaclonal Variation and its Effect on Foliar Epidermal Characters of Caladium humboldtii Schott - Sakpere, A. M. A.; Adedeji, O. (2014)
The ornamental value of Caladium species cannot be overemphasized and tissue culture is increasingly being employed in their propagation. Somaclonal variation is also exploited for the generation of new cultivars for the ornamental market. These variations essentially affect leaf morphology. Therefore, to see if there are corresponding anatomical differences, foliar epidermal studies were carried out on parent plant, Caladium humboldtii Schott, and a somaclonal variant (C. humboldtii 'Sakpere') derived from tuber explants cultured on full strength Murashige & Skoog's (1962) medium supplemented with 3% (w/v) sucrose and 0.4 mg/L 2,4-D combined with 1.0 mg/L kinetin. Morphological differences observed were in the shape and colour of leaves of the in vitro derived plantlets. Foliar epidermal studies revealed significant differences in size of epidermal cells, stomatal index and stomatal size of the parent plant and the somaclonal variant. Circular-shaped stomata were encountered in C. humboldtii, these were sparse to absent in C. humboldtii 'Sakpere'.